You may convert the product `sin(A+B)sin(A-B)` in a sum such that:

`sin(A+B)sin(A-B) = (1/2)*[cos(A+B-A+B) - cos(A+B+A-B)]`

`sin(A+B)sin(A-B) = (1/2)*[cos(2B) - cos(2A)]`

You need to use the formula of cosine of double angle such that:

`cos(2B) -cos(2A) = 2cos^2 B - 1 - 2cos^2 A + 1`

Reducing like terms yields:

`cos(2B)...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

You may convert the product `sin(A+B)sin(A-B)` in a sum such that:

`sin(A+B)sin(A-B) = (1/2)*[cos(A+B-A+B) - cos(A+B+A-B)]`

`sin(A+B)sin(A-B) = (1/2)*[cos(2B) - cos(2A)]`

You need to use the formula of cosine of double angle such that:

`cos(2B) -cos(2A) = 2cos^2 B - 1 - 2cos^2 A + 1`

Reducing like terms yields:

`cos(2B) - cos(2A) = 2(cos^2 B - cos^2 A)`

`sin(A+B)sin(A-B) = (1/2)*[2(cos^2 B - cos^2 A)]`

`sin(A+B)sin(A-B) =(cos^2 B - cos^2 A)`

**Hence, substituting `(cos^2 B - cos^2 A) for sin(A+B)sin(A-B)**

**=> ****(sin(A+B)sin(A-B))/(cos^2(A)cos^2(B)) = (cos^2 B - cos^2 A)/(cos^2(A)cos^2(B)).` **